2021
DOI: 10.1212/wnl.0000000000012191
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Neuroimmunologic, and CSF Investigations in First Episode Psychosis

Abstract: Objectives:To report the neuropsychiatric features and frequency of N-methyl-d-aspartate receptor (NMDAR) and other neuronal IgG antibodies in patients with first episode psychosis (FEP), and assess the performance of reported warning signs and criteria for autoimmune psychosis (AP).Methods:Prospective observational study of patients with FEP assessed for neuropsychiatric symptoms, serum and CSF neuronal antibodies (brain immunohistochemistry, cell-based assays, live neurons), and warning signs and criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
3
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 49 publications
6
78
3
4
Order By: Relevance
“…These findings indicate that, despite an overlap of sNfL levels between pFEP and NMDARe, patients with new-onset psychosis of unclear etiology and serum NfL ≥15 pg/mL had a 120 times higher chance of having NMDARe than pFEP. Considering the clinical setting in which the a priori chance of NMDARe is considerably lower than that of psychosis of psychiatric etiology (estimated prevalence of NMDARe in FEP 3% 2 ) and using the indicated sNfL sensitivity and specificity, the estimated positive predictive value of a patient with a first episode of psychosis and sNfL >15 pg/mL having NMDARe would be 40%, and the negative predictive value would be 99.5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that, despite an overlap of sNfL levels between pFEP and NMDARe, patients with new-onset psychosis of unclear etiology and serum NfL ≥15 pg/mL had a 120 times higher chance of having NMDARe than pFEP. Considering the clinical setting in which the a priori chance of NMDARe is considerably lower than that of psychosis of psychiatric etiology (estimated prevalence of NMDARe in FEP 3% 2 ) and using the indicated sNfL sensitivity and specificity, the estimated positive predictive value of a patient with a first episode of psychosis and sNfL >15 pg/mL having NMDARe would be 40%, and the negative predictive value would be 99.5%.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicate that serum NfL testing can be an important diagnostic aid in these clinical settings, but it does not override the need of comprehensive neurologic evaluation along with brain MRI, EEG, and serum NMDAR antibodies, as recently proposed. 2 If serum NfL levels are ≥15 pg/mL or any of the other tests are abnormal, patients with new-onset psychosis without a clear etiology should undergo a neurologic examination and workup, including CSF analysis for NMDAR antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollak et al proposed a novel and conservative approach to recognize autoimmune psychosis ( 16 ). However, it was found that the criteria for autoimmune psychosis have limited utility in the absence of neurological symptoms or when paraclinical test results are normal ( 17 ). Another study had revealed that anti-NMDA-receptor encephalitis as defined by consensus criteria rarely occurred in psychiatric patients ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS, IgG NR1 antigen-antibody binding results in reversible titratable internalisation of the NMDAR that reduces NMDA signalling and results in the symptom development. Antibody presence in the serum alone is not sufficient to cause symptoms (3,4,7). However, processes disrupting the blood-brain barrier can allow antibody circulation within the CSF, leading to antigen-antibody binding (4).…”
Section: Introductionmentioning
confidence: 99%